A method for obtaining the required system reliability level by applying preventive maintenance. (July 2015) - Pilch, Robert
This work presents a method for determining the reliability of k out of n systems, in which elements are preventively replaced. The presented method is based on a computer simulation whose assumptions and course are discussed in the work. The reliability function is determined for an assumed time horizon with specified probability of failure time distribution and specified preventive replacement periods. The solutions presented in the literature focus mainly on determining the optimum replacement time interval due to expected maintenance costs. The model developed here enables one to observe the effects of performed preventive replacements as changes of reliability function. It also enables one to state whether the preventive replacement periods that were applied can ensure the achievement of the required reliability limit and to check how the changes of fixed values of replacement periods influence the reliability of the whole system. According to the model developed, numerical calculations were made and their results are presented. An example of a practical application of the developed model in the industry is also presented.